Luz e escuridão: presenças de Freud e Klein em O aprender com a experiência de Bion - Cavalcante, Ricardo Almeida (2018)
This research aims at the mapping of continuities and radical discontinuities – the transformations – that the book Learning from experience, published by Wilfred Bion in 1962, stands before the legacies of Sigmund Freud and Melanie Klein. It is the construction of a long ‘Freudo-Kleinian’ road that will serve as a sort of introduction to get to the Bionian work. We take as a metaphor the dialectic between Light and Darkness present in metapsychological, epistemological thinking and in psychoanalytical technique that emerges already from the beginnings of Freud’s thinking, in the turn this author promotes between 1895, in his Project for a scientific psychology, and 1900 in The interpretations of dreams. If in the first work, posthumously published, there is a goal of providing a psychology that is a natural science that can represent psychic processes as clear and free from contradiction, in the book of 1900 the author evokes Virgil in his subtitle: Flectere si nequeo superos, Acheronta movebo, demonstrating his enormous capacity, even at the turn of the century, to name the negative. Melanie Klein, in her turn, brings in her very first production, which goes from 1919 to 1923, a psychoanalytic pedagogy that believes in a prophylaxis linked to the clarification of infantile sexual impulses. But gradually her optimistic and even Enlightened tone will give way and open space for the appointment of highly obscure processes present in the psyche since the most archaic moment of life. Bion can be taken as the most Freudian of the Kleinians. Throughout his work we come across countless times with metaphors to illuminate clinical materials in the absence of patients and the psychoanalyst’s need to place him or herself in a position of darkness during the transferential here-and-now, in the sessions, in the presence of patients. Besides going through his important creations in his 1962 book such as the container-contained and reverie ideas, as well as other important psychoanalytical abstractions that are born there, we will explore the meanings of his technical indications for psychanalysts, during the sessions, namely, to work with an opacity of memory, desire and prior understanding